A chromodomain switch mediated by histone H3 Lys 4 acetylation regulates heterochromatin assembly - Xhemalce, Blerta (Cold Spring Harbor Laboratory Press, 2010)
Chromodomain proteins (Chp1/Chp2/Swi6/Clr4) bind to methylated H3K9 (H3K9me) and regulate pericentric heterochromatin in fission yeast. Chp1 and Clr4 (H3K9-HMT), bind transcriptionally active heterochromatin, whereas Chp2/Swi6 (HP1 homologs) are recruited during the inactive state. We show that H3K4 acetylation (H3K4ac) plays a role in the transition of dimethylated H3K9 (H3K9me2) occupancy from Chp1/Clr4 to Chp2/Swi6. H3K4ac, mediated by Mst1, is enriched at pericentromeres concomitantly with heterochromatin reassembly. H3K4R (Lys → Arg) mutation increases Chp1 and decreases Chp2/Swi6 pericentric occupancy and exhibits centromeric desilencing. Consistent with structural data, H3K4ac specifically reduces Chp1/Clr4 affinity to H3K9me. We propose that H3K4ac mediates a chromodomain switch from Chp1/Clr4 to Swi6/Chp2 to allow heterochromatin reassembly.